Housing Attribute Preferences in Bandung City: A Comparison Between Generation X, Y, Z - Ilma Nurfadlilawati; Hanson E Kusuma (Institute of Research and Community Outreach, Petra Christian University, Indonesia, 2024)
Each generation encounters distinct social, economic, cultural, and technological contexts specific to their era. Moreover, their lifestyles vary, resulting in disparate housing preferences. This study analyzes five housing attribute preferences of Generation X, Generation Y, and Generation Z: Economic attribute, location and accessibility attribute, physical attribute, environment attribute, and social attribute. The research uses a stated preference approach. The study uses a mixed method and a stated preference approach while collecting data by online questionnaire. Three analytical techniques are employed in this research: correspondence analysis to identify differences in dwelling type preferences among generations, PCA and FA to identify the underlying housing attribute influencing housing preferences, and ANOVA to analyze housing attribute dimensions with significant differences among generations. The analysis result reveals that each generation tends to prefer Landed Housing. The housing attribute dimensions that are the main priority among generations are Utilities, Infrastructure, and Environmental Quality. Meanwhile, significant differences in housing preferences between Generation X, Generation Y, and Generation Z are found in the space comfort and social interaction dimensions.